Evaluation of Performance and Authentic in the Model by Competences in Secondary: A Mixed Study - Aliosha Alderete Martínez; Katherina Edith Gallardo (Universidad Autónoma de Madrid, 2018)
This article presents results from an educational research process about the application of some principles of performance and authentic assessment in secondary level in the subject of History related to satisfaction and change of meaning about assessment of students. The objective follows the intention of understanding the impact of students after the application of those principles in the framework of Competency-based education model, considered one of the most important educational changes of this decade within most of the Latin-American countries in educational systems. A Mixed-method study was made in a public school. A group of 35 students from second year participated. Three instruments were developed for data collection purposes: A performance rubric, an interview as well as a questionnaire. The results achieved in terms of perception of the use and application of authentic evaluation and performance allow inferring that students experimented satisfaction with these new assessment process and feedback giving. It was also analyzed that students' grades reached higher level, including those students with low performance at the beginning of the study. Lessons learn and research needs in this topic are further discussed.